ANALISIS ATRIBUT PRODUK SAMSUNG DAN ASUS MENGGUNAKAN METODE MULTIDIMENSIONAL SCALING (MDS) DI BANDAR LAMPUNG - Aswin Aswin; Aega Wahidun (Jurnal Bisnis Darmajaya, 2016)
The aim of this study was to analyze and know the Samsung and Asus amartphone product attribute positioning map based on consumers’  perception in Bandar Lampung. The Basis used to map smartphone products was consumers’ perception to the similarity of shape, feature, work quality, quality image, endurance, validity, repairation, style and design in each of smartphones. The analysis technique used was Multidimensional Scalling through SPPS 21.0. The samples in this research was 100 respondents in Bandar Lampung through purposive sampling method. The data obstained was tested using by MDS analysis to know the validity and reability. Based on the analysis result there were similarity on each of smartphone attributes, they such as shape, work quality endurence, validity, style and design. The attribute was not similar were feature and repair based on consumers’ perception. The result of consistency and respondent behavior similarities showed that respondents didn’t  have the behavioral similarity in evaluating each of smartphone products.Key Word: Product Atrribute, Positioning Map, Samsung, Asus, Multidimensional Scaling